Reproduction Performance, Serum Biochemical and Growth Indices of Grower Rabbits (Oryctolagus cuniculus) fed Sheabutter (Vitellaria paradoxa C.F. Gaertn.) Nut Meal (2018)
There are reports of possible world food shortage especially animal products which are veritable sources of essential nutrients required by human beings. This threat could be averted if rabbit production is increased due to its unique prolificacy, short generation interval and quick return on investment. Unfortunately, there are inadequate qualitative and quantitative feedstuffs hence, the quest for unconventional feedstuff to reduce competition with human beings for conventional food/feedstuff. The aim of this study was to investigate the influence of graded levels of sheabutter nut meal on reproduction performance, serum biochemical indices and growth indices of grower rabbits. Sixty grower rabbits (1 buck: 1 doe ratio) weighing about 1kg at 7 weeks of age were randomly allocated to treatments D1 (0.0% SNM), D2 (2.0% SNM), D3 (4.0% SNM), D4 (6.0% SNM) and D5 (8.0% SNM) such that each treatment had twelve rabbits. Sheabutter nut meal was collected from sheabutter nut milling centres in Lafia metropolis and used in formulating feed for the experimental animals. Sample of sheabutter nut meal was used in proximate analysis. Data were collected on body weight, morphometric traits, conception percentage and at the end of the experiment, blood samples were collected and processed for serum biochemical indices. Results showed that the animals gained weight ranging from 0.1 to 0.26g with the highest in control treatment. The body length varied from 0.22cm in D4 to 0.33cm in D3 and the girth circumference ranged from 0.26 to 0.36cm. While the albumin was highest (29.2g/l) in control, the creatinine was lowest (70.0µmol/l) in D4, the urea varied from 3.13 to 8.7µmol/l, cholesterol (2.9 to 3.85mmol/l), triglyceride (0.83 to 0.98mmol/l) and blood glucose was superior (1.36mmol/l) in D2. Since sheabutter nut meal did not seemingly influence the physiological wellbeing of the treated rabbits it could be utilized up to 8%.